2016
DOI: 10.1038/srep28538
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of refractory cutaneous ulcers with mixed sheets consisting of peripheral blood mononuclear cells and fibroblasts

Abstract: The purpose of this study was to confirm the therapeutic effects of mixed sheets consisting of peripheral blood mononuclear cells (PBMNCs) and fibroblasts on cutaneous skin ulcers. Vascular endothelial growth factor (VEGF) secretion in mixed cell sheets was much higher than in PBMNCs and fibroblasts. Concerning the mechanism, transforming growth factor beta 1 and platelet-derived growth factor BB secreted from PBMNCs enhanced VEGF production in fibroblasts. In wounds created on the backs of diabetic mice, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…We previously reported that mixed-cell sheets consist of autologous fibroblasts (1.25 × 10 5 cells) and PBMNCs (2.0 × 10 6 cells) on UpCell® 24-well plates [26]. To determine the maximum possible number of fibroblasts to configure mixed-cell sheets on these plates, we examined the number of fibroblasts present when the number of PBMNCs remained at 2.0 × 10 6 cells/well.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that mixed-cell sheets consist of autologous fibroblasts (1.25 × 10 5 cells) and PBMNCs (2.0 × 10 6 cells) on UpCell® 24-well plates [26]. To determine the maximum possible number of fibroblasts to configure mixed-cell sheets on these plates, we examined the number of fibroblasts present when the number of PBMNCs remained at 2.0 × 10 6 cells/well.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we attempted to make multilayered sheets on a typical culture dish and detach them using a small amount of dispase. With this method, the multilayered sheets incorporated a subset of PBMMCs as in our previous study [26], and the population of PBMNCs was considered to contribute to angiogenesis [38]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations